A descriptive study on the usage of performance measure according to balanced scorecard (BSC) perspectives within the Malaysian electrical & electronic sector / Amri Mohamad, Tuan Rosli Tuan Hassan dan Yusserie Zainuddin - Mohamad, Amri; Tuan Hassan, Tuan Rosli; Zainuddin, Yusserie (Universiti Teknologi Mara Cawangan Kelantan, 2016)
This research presents the use of multiple measures of performance in the electrical and electronic (E&E) manufacturing firms in Malaysia. The objective of this study is to investigate the usage of multidimensional performance measure which includes financial and nonfinancial indicators within the Malaysian E&E manufacturing firms’ performance. Basically, the theoretical gaps concentrated on the issue of focusing solely on financial measurements to measure the firm’s performance. This is to investigate the usage of performance measure according to the Balanced Scorecards (BSC) perspectives within the E&E manufacturers in Malaysia.